2019
DOI: 10.18092/ulikidince.464537
|View full text |Cite
|
Sign up to set email alerts
|

Audit Quality and Earnings Management: Evidence From Turkey

Abstract: A b s t r a c tEarnings management is one of the controversial issues in the current business environment. The value relevance of earnings is adversely influenced by earnings management. The objective of this study is to analyze the association between audit quality and earnings management for non-financial firms quoted on Borsa Istanbul. Ordinary least square regression analysis is employed in this study in analyzing the association between earnings management and audit quality. Three different proxies for au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Lopez and Vega (2019) indicate that firms audited by more specialized Certified public accountants (CPAs) tend to have lower degrees of discretionary accruals. Additionally, Ozcan (2019) addresses the association between audit industry specialization and earnings management for a sample of 97 nonfinancial firms listed on Borsa Istanbul, and provides evidence that audit industry specialization significantly and adversely affects earnings management. Consistently, Jayeola et al (2017) identify a negative association between audit industry specialization and earnings management in the context of Nigerian banking sector.…”
Section: Audit Industry Specialization and Earnings Managementmentioning
confidence: 99%
“…Lopez and Vega (2019) indicate that firms audited by more specialized Certified public accountants (CPAs) tend to have lower degrees of discretionary accruals. Additionally, Ozcan (2019) addresses the association between audit industry specialization and earnings management for a sample of 97 nonfinancial firms listed on Borsa Istanbul, and provides evidence that audit industry specialization significantly and adversely affects earnings management. Consistently, Jayeola et al (2017) identify a negative association between audit industry specialization and earnings management in the context of Nigerian banking sector.…”
Section: Audit Industry Specialization and Earnings Managementmentioning
confidence: 99%
“…Furthermore, the relationship between AAT and FRQ has been investigated in previous studies using a variety of proxies such as auditor independence (Abubakar et al, 2020;Ihsan et al, 2016), established a positive connection amid AI and FRQ, audit fees AF and FRQ (Huang & Hsiao, 2011;Wuchun et al, 2014;Al Dabbous et al, 2015;Al-rassas & Kamardin, 2015;Habbash & Alghamdi, 2016;Kuntari et al, 2017;Reguera-alvarado et al, 2019;Scott, 2020), auditor tenure AT (Jorjani & Gerayeli, 2018;Olufemi & Patrick, 2018;Özcan, 2018;Sarun et al, 2019;Cameran et al, 2020) and joint audit JA (Zerni et al, 2014;Al Dabbous et al, 2015;André et al, 2015;El Assy, 2015;Velte & Azibi, 2015;Haak et al, 2018;Sabah et al, 2019).…”
Section: Ejmssmentioning
confidence: 99%
“…(2020); Lopes (2018), Surbakti and Shaari (2018); Priharta and Rahayu (2019); it was determined that element of CG mechanisms jointly reduce EM. Furthermore, Özcan (2019) found that CG mechanisms significantly and negatively related with likelihood of EM. These studies documented that the CG mechanisms lower the level of EM.…”
Section: Introductionmentioning
confidence: 99%